PENGEMBALIAN KERUGIAN NEGARA AKIBAT TINDAK PIDANA KORUPSI (STUDI KASUS DI KEJAKSAAN NEGERI PELALAWAN) - Roby Azhari; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In Law Number 31 Year 1999 Jo of Law Number 20 Year 2001 Concerning the Eradication of Corruption which has been regulated in Article 18 paragraph (1) Part b About Additional Criminal which obliges the corruptor to return state loss as much as equals objects obtained from criminal acts of corruption. The purpose of this thesis Writing, namely: First, the return of state losses due to criminal acts of corruption committed in the State Prosecutor Pelalawan, Second, the obstacles faced by the State Prosecutor Pelalawan in returning state losses due to corruption. This type of research can be classified in the type of sociological juridical research because in the research the authors directly conduct research on the place to be studied, while the population and sample is the whole party related to the problems studied in this study, data sources used, primary data, secondary data , data collection techniques in this study by interviews, literature review. From the results of this study can be concluded. First, the return of state losses due to corruption crimes committed in the Pelalawan District Attorney through the payment of replacement money for every defendant of corruption cases is not in accordance with the provisions of Article 18 paragraph (1) sub-paragraph b of Law Number 31 Year 1999 Jo Law Number 20 Year 2001, that is, the repayment of the replacement amount is as much as the property obtained from corruption, Second, the obstacle faced by the Pelalawan District Attorney in returning the state losses due to corruption due to the lack of personnel of the Public Prosecution Service especially the Pidsus and the intelligence, the lack or the lack thereof budget in handling corruption crime, especially in conducting the asset tracking and also the authority of the prosecutor is limited by law or law itself. Keywords: Public Prosecutor - Corruption - Refund - State Losses